Osteoporotic Goat Spine Implantation Study Using a Synthetic, Resorbable Ca/P/S-Based Bone Substitute - Yang, Bing-Chen; Lan, Sheng-Min; Ju, Chien-Ping; Chern Lin, Jiin-Huey (Frontiers in Bioengineering and Biotechnology, 2020)
One primary purpose of the present study is to clarify whether the highly porous, resorbable Ca/P/S-based bone substitute used in this study would still induce an osteoporotic bone when implanted into the osteoporotic vertebral defects of ovariectomized (OVX) goats, or the newly-grown bone would expectantly be rather healthy bone. The bone substitute material used for the study is a synthetic, 100% inorganic, highly porous and fast-resorbable Ca/P/S-based material (Ezechbone® Granule CBS-400). The results show that the OVX procedure along with a low calcium diet and breeding away from light can successfully induce osteoporosis in the present female experimental goats. The histological examination reveals a newly-formed trabecular bone network within the surgically-created defect of the CBS-400-implanted (OVX_IP) goat. This new trabecular bone network in the OVX_IP goat appears much denser than the OVX goat and comparable to the healthy control goat. Histomorphometry show that, among all the experimental goats, the OVX_IP goat has the highest trabecular thickness and lowest trabecular bone packet prevalence. The differences in trabecular plate separation, trabecular number and trabecular bone tissue area ratio between the OVX_IP goat and the control goat are not significant, indicating that the trabecular bone architecture of the OVX_IP goat has substantially recovered to the normal level in about 6 months after implantation without signs of osteoporosis-related delay in the bone maturing process. The quick and nicely recovered trabecular architecture parameters observed in the OVX_IP goat indicate that the present Ca/P/S-based bone substitute material has a high potential to treat osteoporotic fractures.